A Case of Bronchial Asthma Induced by Direct Inhalation of a Chironomid Midge, Tanytarsus oyamai Sasa, 1979 - Sasa, Manabu; Igarashi, Takao; Watanabe, Hiroyuki; Mizukami, Youshin; Murakami, Gyokei; Kawai, Koichiro (Nihon Kyōbu Shikkan Gakkai zasshi, 1986)
A 19 year-old female patient was hospitalized due to a severe attack of bronchial asthma which occurred about 30 minutes after inhaling midges. She was jogging on a road surrounded by rice paddies at about 8p.m. on June 17th 1985, when she encountered a swarm of midges, and realized she had inhaled a few of them into the trachea. About 30 minutes later, she had a severe attack of dyspnea, called an ambulance and was admitted to Toyama City Hospital at 9:30 as an emergency case. Arterial blood gas analysis revealed remarkable hypoxemia of PaO2, 39.9 torr and hypercapnea of PaCO2 47.1 toor. She was treated with neophylline 250mg DIV and hydrocortisone 500mg with an i. v. push. Her condition gradually improved and 12 hours later the arterial blood gas level became normal. The specimens inhaled by the patient could not be recovered, but the midges found swarming on the same spot on next day were identified as composed of males and females of Tanytarsus oyamai Sasa 1979. This is a species widely distributed in rice paddies and ponds of various regions of Japan, and represented by far the largest numbers among the chironomid species collected in a rice paddy area in Tokushima reported by Kikuchi and others. An extract prepared from the samples of this species collected at the same place as the patient inhaled the midge caused strong immediate type skin reaction when applied on the arm of the same person, and also caused a strong positive reaction by the inhalation provocation test carried out on the same person on 8 July 1985. Her serum was examined with RAST to Tanytarsus oyamai and showed a positive high score.